Minimizing Page Fault Using Queueing Theory - Biswas, S; Sengupta, D; Bhattacharjee, R; Handique, M (International Journal of Computer Sciences and Engineering, 2015)
In this paper we recommend a compelling approach to minimize page fault rate utilizing the hypothesis of waiting lines, i.e. Queuing Theory. The Queuing Theory has wide applications such as making business decision, hospital management, traffic regulation etc. but in this paper we are simply using it to reduce the number of page faults. Hence for the said purpose a comparative analysis is made in this paper between the typical performance from ordinary execution of page replacement algorithm and the performance after actualizing these conventional algorithms on the queuing models. Therefore the performance is measured on the basis of page fault rate and the result from this comparative dissection helps us determine conclusion on the effective way of page fault reduction.